Estimating the glomerular filtration rate in pregnancy: The evaluation of the Nanra and CKD-EPI serum creatinine-based equations - Gao, Michael (Obstet Med, 2020)
AIM: To compare the performance of the Nanra and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation for estimating glomerular filtration rate in pregnancy against the 24 h urine creatinine clearance. METHODS: Pregnant women had 24 h urine collections with simultaneous serum creatinine levels. Measured 24 h urine creatinine clearance was compared to two equations: Nanra and CKD-EPI. Level of concordance was measured, with an a priori bias acceptance of ±15 ml/min/1.73 m(2). RESULTS: A total of 53 synchronous urine and serum creatinine samples were analysed. The Nanra equation had a bias of −13.4 ml/min/1.73 m(2) while the CKD-EPI equation had bias of 14.2 ml/min/1.73 m(2). Both equations showed a high degree of proportional error and had poor agreement with 24 h urine creatinine clearance. CONCLUSIONS: None of the equations were shown to reliably measure the estimated glomerular filtration rate in pregnant women. A valid serum creatinine-based estimated glomerular filtration rate equation in pregnancy is yet to be established.